The second front. (Economist, 1998)
On November 17, 1998, a federal judge in San Jose, California, ordered Microsoft to cease shipping its version of Java, an Internet software language owned by Sun Microsystems. The dispute involves a licensing agreement for Java, signed in 1996 by Microsoft and Sun. By October 1997, Sun had filed a suit claiming that Microsoft violated the agreement by adapting its version of Java so that it was only compatible for Microsoft's Windows operating system. According to Sun, this would destroy the language's claim that it could be used on any system, the main attraction of the language to programmers. Microsoft claims, however, that its alterations were only for the good of the consumer because its adaption of Java made programs written in the language run better on Windows.